Contemporary Debates in Holocaust Education - Gray, Michael; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Holocaust education is a rapidly evolving and controversial field. This book, which critically analyses the very latest research, adopts a global perspective and discusses a number of the most important debates which are emerging within it such as teaching the Holocaust without survivors and the role of digital technology in the classroom.
Keywords: Science; Science; Science, general